Dialektika Esensi Filsafat, Teologi, dan Tasawuf dalam Keilmuan Islam - Zuhur Diana; Irma Dwi Amalia; Imron Rossidy (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The study of Islamic thought on philosophy, theology, and Sufism has been the subject of controversial and contentious discussion. These three Islamic thoughts are mutually distinguished and separated as if they are unrelated to each other. In fact, if traced historically, there is a continuous and complementary relationship. This study aims to explore the dialectic of the essence of philosophy, theology, and Sufism according to an Islamic perspective. The method used through a descriptive qualitative approach with library research for collecting data, whereas techniques analyzed data using historical and philosophical analysis. The results of this study show that there is a dynamic essential dialectic between philosophy, theology, and Sufism in Islamic scholarship. Although the methods used are different, these three disciplines are interrelated and have the same goal of seeking the ultimate truth and understanding God's existence and His relationshipwith the universe. The relationship between the three involves dynamic dialogue and debate, philosophy provides a rational framework, theology provides a framework of religiosity, and Sufism adds a spiritual dimension. These three are the main pillars in Islamic scholarship that interact and corelate each other to achieve the same ultimate goal, which is to complement each other and together form a holistic understanding of God and truth in Islamic scholarship.